A comprehensive overview of the relationship between RET gene and tumor occurrence - Zhao, Lu; Wang, Na; Zhang, Dou; Jia, Yingjie; Kong, Fanming (Frontiers in Oncology, 2023)
RET is a transmembrane receptor protein-tyrosine kinase that plays significant roles in nervous system and many other tissues. Point mutation or gene fusion of RET, enhanced PI3K/AKT, RAS/RAF, MAPK, PLCg paysways, which promote cell proliferation, growth, and survival. Great efforts have been made in the treatment of against RET. Selpercatinib and Pralsetinib were approved by FDA in 2020, which achieved a major breakthrough in this field. This article systematically reviewed RET gene and its biology as well as oncogenic role in multiple cancers. Moreover, we also summarized recent advances in the treatment of RET, and the mechanism of drug resistance.